The patterns of land ownership in Johore Bahru (particularly at Jalan Wong Ah Fook, Jalan Siu Nam, Jalan Meldrum, Jalan Ngee Heng, Jalan Gereja, Jalan Station dan Jalan Sulaiman) / How Lee Pheng - How , Lee Pheng (1985)
The research is concerned with the patterns of land ownership in the town of Johore Bahru. The centre of discussion will be on Jalan Wong Ah Fook, Jalan Siu Nam, Jalan Meldrum, Jalan Gereja, Jalan Sulaiman, Jalan Station and Jalan Ngee Heng . Sub-roads such as Jalan Gereja, Jalan Station and Jalan Sulaiman are included as these are situated together in the town centre. Altogether there are six chapters. Chapter I deals with the introduction. The writer discusses the scope of the research, methods and problems encountered during the research. Chapter II gives a brief account of the pre sent condition of Johore Bahru and a concept related to the study. In Chapter III the writer discusses the patterns of final ownership according to various categories of owners and the transfer to land. Included in this chapter are land owned by private owners, companies, banks, associations and Government. Chapter IV is about the patterns of ownership according to ethnicity. The ethnic groups are Malaysa, Chinese and Indians. A discussion on comparison between ethnic groups and companies is also included. Chapter V concerns the change in patterns of ownership in the initial stage and final stage. Here, the writer touches on the changes in transfers among various categories of owners and ethnic groups. In chapter VI the writer draws her conclusions based on the findings from the previous chapters. The relation between the study of land ownership and the concept of capital efficiency is given to show disquilibrium in land owned by the various categories of owners.